2020
DOI: 10.1101/2020.11.08.20227744
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Public Health response to an outbreak of SARS-CoV2 infection in a Barcelona prison

Abstract: An outbreak of SARS-CoV2 infection in a Barcelona prison was studied after seven cases appeared in nine days. One hundred and eighty-four people (148 inmates and 36 prison staff) were evaluated by rt-PCR. Thirty-nine (24.1%) were positive: 33 inmates and six staff members. The inmates were isolated in prison module 4, which was converted into an emergency COVID unit. Two people (one inmate and one health worker) were admitted to hospital for clinical deterioration. There were no deaths. Outbreaks pose a huge r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…York City, USA jails in March and April 2020 [59], and 0.0% (0/46) in a penitentiary in Barcelona, Spain [27].…”
Section: Plos Onementioning
confidence: 99%
“…York City, USA jails in March and April 2020 [59], and 0.0% (0/46) in a penitentiary in Barcelona, Spain [27].…”
Section: Plos Onementioning
confidence: 99%
“…Regarding factors associated with COVID-19 infection, a study in a correctional facility in Arkansas, USA, in April and May 2020 found that pre-existing chronic lung disease was associated with infection, but other pre-existing medical conditions (hypertension, diabetes, cardiovascular disease, chronic kidney disease, chronic liver disease) were not [49]. In a prison in Barcelona, Spain, age, history of diabetes, and HIV infection, respectively, were not associated with infection [27]. In an outbreak in a Texas prison in July and August 2021, vaccination status and diabetes were associated with infection [35].…”
Section: Number Of Casesmentioning
confidence: 99%